Mary Anne's bad luck mystery - Martin, Ann M.; Cheng, Cynthia Yuan (2023)
"Mary Anne should never have thrown away that chain letter she got in the mail. Ever since she did, bad things have been happening to everyone in the Baby-sitters Club. With Halloween coming up, Mary Anne's even more worried -- what kind of spooky thing will happen next? Then Mary Anne finds a new note in her mailbox: Wear this bad-luck charm, it says. OR ELSE. Mary Anne has to follow the note's instructions. But who sent the charm? And why did they send it to Mary Anne? The BSC might never see an end to their bad luck if they don't solve this mystery soon!"--
Ages 8-12
Grades 4-6